Green Extractivism and the Crisis of Spatial Justice: Indigenous Land Conflict within the Morowali Nickel Industrial Corridor - Abdul Rahman Hamid; Wicipto Setiadi; Taufiqurrohman Syahuri (PT FORMOSA CENDEKIA GLOBAL, 2026)
The global energy transition has increased demand for transition minerals, particularly nickel, as a strategic component in electric vehicle battery production and low-carbon energy systems. Indonesia has positioned itself as a global nickel hub through downstream industrialization policies and the development of the Indonesia Morowali Industrial Park (IMIP). However, the rapid expansion of the nickel industry in Morowali has also triggered environmental degradation, agrarian conflict, and indigenous land dispossession. This study aims to analyze the relationship between green extractivism, spatial planning, agrarian conflict, and indigenous land rights within the Morowali nickel industrial corridor. The research employs a socio-legal approach with a political ecology perspective using qualitative analysis. Data were collected from spatial planning documents, mining regulations, scientific journals, media reports, and publicly available interviews involving indigenous communities, academics, and government institutions. The findings indicate that nickel industrial expansion has produced spatial injustice through land-use change, mining concession expansion, and industrial zoning that marginalize indigenous communities and local living spaces. Spatial planning instruments function not as neutral governance tools but as mechanisms legitimizing green extractivism and land dispossession. This study contributes to spatial planning law by integrating environmental justice, political ecology, and socio-legal studies in understanding the spatial crisis within Indonesia’s transition mineral industry.